Policy challenges on mercury use in Ghana's artisanal and small-scale mining sector - Nyame, F.K. (International Journal of Environment and Pollution, 2010)
Mercury use in Ghana's Artisanal and Small-scale Mining (ASM) sector is a growing problem owing to the increasing numbers of people involved, locations of operation, extent of possible contamination of the natural environment and its impact on human health. For over two decades, many local and internationally-coordinated initiatives undertaken to mitigate its harmful effects in ASM communities have been mostly unsuccessful due to absence of alternative options acceptable for gold recovery and inadequate awareness of the short- and long-term health effects of mercury use. This paper examines major policy challenges in minimising mercury use in Ghana's ASM sector, arguing that a coordinated, integrated and sustained approach offers better promise in tackling the problem. Copyright © 2010 Inderscience Enterprises Ltd.
Keywords: Ghana; Mercury; Small-scale gold mining; Solutions